ANALISIS AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK DAUN YODIUM (Jatropha multifida L.) DENGAN METODE CUPRIC ION REDUCING ANTIOXIDANT CAPACITY (CUPRAC) - St Maryam; Randi Pratama; Nurmaya Effendi; Tadjuddin Naid (Jurnal Fitofarmaka Indonesia, 2015)
The research had been conducted about the analysis of antioxidant activity of yodium (Jatropha multifida L.) leaves using cupric ion reducing antioxidant capacity to determine the existance of antioxidant activity and to measure the antioxidant capacity in yodium (Jatropha multifida L.) leaves ethanolic extract using CUPRAC method. It was experimental research using CUPRAC method to prove the existance of antioxidant activity of yodium (Jatropha multifida L.) leaves. It was started by extracting the leaves using maseration using ethanol 96% solvent. The resulted extracts were analyzed quantitatively and qualitatively by adding CuCl2 solution, neucuproin, NH4Ac buffer system which were measured in UV-Visible spectrophotometer and analyzed at a wavelength of 450 nm. Based on data analysis, it was found that the askorbat acid equivalent (AAE) presentage of yodium (Jatropha multifida L.) leaves was 0.7385 ± 0.0521 mg L-1 AA g-1 extract.